2021
DOI: 10.34172/doh.2021.31
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Hospitalization and Length of Hospitalization of the Patients with Covid-19

Abstract: Background and Objectives Although a significant number of Covid-19 patients tend to be hospitalized, few studies have explored the factors related to the hospitalization of these patients. This study was conducted to investigate the factors affecting the hospitalization and duration of hospitalization of the patients with Covid-19 in Shohada Imam Hossein Hospital in Tehran in the first half of 2020. \ Material and Methods This cross-sectional study was performed by convenience sampling method. Data were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…According to the present findings, old age was associated with higher mortality rates and longer hospital stays. This is consistent with other studies that have identified age as a significant predictor of both mortality and hospital length of stay 7,19,25 . In a retrospective, multicenter cohort study conducted in China, patients who died from COVID‐19 had a mean age of approximately 69 years, which was significantly higher than those who survived 7 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…According to the present findings, old age was associated with higher mortality rates and longer hospital stays. This is consistent with other studies that have identified age as a significant predictor of both mortality and hospital length of stay 7,19,25 . In a retrospective, multicenter cohort study conducted in China, patients who died from COVID‐19 had a mean age of approximately 69 years, which was significantly higher than those who survived 7 .…”
Section: Discussionsupporting
confidence: 90%
“… 19 , 20 However, in Saudi Arabia, the mean duration was 6 days, 5 while patients not admitted to the ICU in the United States had a mean duration of 6 days. 21 In France, Peru, the Mediterranean, London, and Tehran, the mean hospital LOS was respectively 9, 22 7, 22 8.5, 23 6, 24 and 7.5 days 25 These variations in hospital stay could be attributed to differences in countries, geographical regions, health facilities, and the severity of patients' conditions. 26 Other demographic factors, such as age, may also contribute to these differences.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The present study showed that age, after the biorhythm, is the most important factor in predicting the number of hospitalized days for diabetic patients with COVID-19. Other studies have also con rmed the effect of the age factor on the length of hospitalization for diabetic, cardiac, COVID-19 patients, and the elderly (29)(30)(31)(32)(33) This is happening while aging populations represent one of the most important features of the 21st century. In the near future, almost all developed and developing countries will experience a rapid expansion of their aging and elderly populations.…”
Section: Discussionmentioning
confidence: 94%